Hydrophilic anionic binder as well as preparation method and application thereof

By introducing piperidine groups and hydrophilic groups on the main chain of the anionic binder, an anionic binder with high stability and hydrophilicity was prepared, which solved the problem of poor water absorption performance and achieved efficient ion transport and material adaptability.

CN120519114APending Publication Date: 2025-08-22TIANJIN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510647279.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-20
Publication Date
2025-08-22

AI Technical Summary

Technical Problem

The existing anionic binders have poor water absorption performance in electrolytic cells and fuel cells, making them difficult to have both hydrophilicity and stability, which affects the ion transport efficiency and the adaptability of materials.

Method used

By introducing piperidine groups as side chains on the main chain and combining hydrophilic groups, an anionic binder with a three-dimensional structure is prepared to enhance its water absorption and ionic conductivity, and form a highly stable and hydrophilic anionic binder.

Benefits of technology

It improves the water absorption and ionic conductivity of anionic binder, improves the chemical stability and mechanical strength of the material, and ensures the continuous stability and efficiency of the electrochemical reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120519114A_ABST
    Figure CN120519114A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydroxyl conductive polymer materials, and discloses an anionic binder with hydrophilicity and dispersity as well as a preparation method and application of the anionic binder. A piperidine group is used as a side chain to be connected to a main chain with three-dimensional conformation, an increased free volume between the main chains provides a space for water molecules to enter, and meanwhile, the hydrophilicity (water absorption) of the ionomer is enhanced by retaining a hydrophilic group on a main chain skeleton; the anionic binder with high cohesiveness, stability and hydrophilic performance is obtained, and meanwhile, the anionic binder has excellent ionic conductivity. The obtained anionic binder can be dissolved in an organic solvent to obtain a high-dispersity anionic binder solution. The obtained anionic binder solution and catalyst particles are prepared into uniform catalyst ink, the catalyst ink is sprayed on a substrate, and a catalyst layer covered with the hydrophilic anionic binder can be obtained after the low-boiling-point solvent is dried.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydroxide conductive polymer materials, and in particular relates to a hydrophilic anionic binder and a preparation method and application thereof. Background Art

[0002] With the rapid development of hydrogen energy storage technology, anion exchange polymer binders are being widely studied as novel functional materials in the electrochemical energy field. These polymers, characterized by cationic functional groups, demonstrate unique anion-selective transport properties and hold great promise for applications in cutting-edge new energy technologies such as alkaline fuel cells, hydrogen production from water electrolysis, carbon dioxide electroreduction, and flow batteries. They also hold a key position in traditional industries such as the chlor-alkali industry, heavy metal recovery, water treatment, and hydrometallurgy. To meet practical application demands, current research focuses on improving the core performance of anion exchange membranes: on the one hand, addressing technical bottlenecks in ionic conductivity and chemical stability, and on the other, developing functionalized materials for specific application scenarios. For example, on the cathode side of anion exchange membrane electrolyzers, materials must possess both excellent hydrophilicity and ion transport efficiency, placing higher demands on the precise design of polymer molecular structures and the targeted modification of functional groups. This application-oriented performance optimization research is driving the leapfrog development of anion exchange binders from basic materials to engineered solutions.

[0003] Some currently commercialized anionic binders, such as FuMA-Tech and Piperion series products, have electrical conductivity that can meet the basic requirements for use in anion exchange membrane fuel cells and alkaline electrolytic cells. Patent CN115558088A discloses a class of piperidine tertiary amine group polymers based on a carbon-based skeleton spatial entanglement structure and its applications. The invention forms an entangled molecular cross-linking structure, which makes the prepared material have extremely excellent mechanical strength and elongation. At the same time, the reduction of the crystalline area improves the ionic conductivity of this type of membrane material. However, in order to limit the swelling of the polymer material, the water absorption of these binders is very low. In order to further improve the adaptability of specific application scenarios, it is necessary to develop binder materials that are both hydrophilic and stable. Summary of the Invention

[0004] This invention addresses the technical issue of poor water absorption by anionic binders in practical use in electrolyzers and fuel cells, providing a hydrophilic anionic binder, its preparation method, and its application. Piperidine groups are attached as side chains to a main chain with a three-dimensional conformation. The increased free volume between the main chains provides space for water molecules to enter. The retention of hydrophilic groups on the main chain skeleton enhances the hydrophilicity (water absorption) of the ionomer, resulting in an anionic binder with high adhesion, stability, and high hydrophilicity, while also exhibiting excellent ionic conductivity.

[0005] The anionic binder obtained above can be dissolved in an organic solvent to obtain a highly dispersible anionic binder solution. The obtained anionic binder solution is mixed with catalyst particles to form a uniform catalyst ink, which is sprayed onto a substrate. After the low-boiling-point solvent dries, a catalyst layer covered with the hydrophilic anionic binder is obtained.

[0006] In order to achieve the above-mentioned object of the invention, the present invention is implemented through the following technical solutions:

[0007] According to one aspect of the present invention, a method for preparing an anionic binder having both hydrophilicity and dispersibility is provided, the method being carried out according to the following steps:

[0008] (1) polymerizing a branching agent, a monomer containing a hydrophilic group, an aromatic monomer, and a monomer containing a piperidinone group in a polymerization solvent to obtain a polymer having hydrophilicity and a three-dimensional structure;

[0009] (2) reacting the polymer obtained in step (1) with an ionizing agent in an ionizing solvent under light-shielding conditions to obtain an anionic binder solid having cationic side chains;

[0010] (3) dissolving the anionic binder solid obtained in step (2) in an organic solvent to obtain a fully dispersed hydrophilic anionic binder solution.

[0011] Furthermore, the branching agent is at least one of the monomers represented by formula (1) and formula (2); the monomer containing a hydrophilic group is a monomer represented by formula (3); the aromatic monomer is at least one of the monomers represented by formula (5), formula (6) and formula (7); the monomer containing a piperidone group is a monomer represented by formula (4);

[0012]

[0013] wherein R1 and R2 in formula (3) are each independently selected from any one of phenol, catechol, o-cresol, resorcinol, toluene, methanol, 1-ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, 1-heptanol, 1-octanol, and methoxymethyl;

[0014] Wherein, R3 in formula (4) is selected from any one of hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl or phenyl;

[0015] Wherein, n in formula (5) is an integer from 0 to 10;

[0016] Here, n in formula (6) is an integer from 1 to 20.

[0017] Furthermore, the monomer containing a hydrophilic group is one of bisphenol fluorene, 9,9-bis(3,4-dihydroxyphenyl)fluorene, 9,9-bis(3-methyl-4-hydroxyphenyl)fluorene, 9,9-bis(6-hydroxy-2-naphthol)fluorene, and 9-fluorenylmethanol.

[0018] Furthermore, the monomer containing a piperidone group is at least one of N-methyl-4-piperidone, N-ethyl-4-piperidone, N-propyl-4-piperidone, 4-piperidone or N-isopropyl-4-piperidone.

[0019] Furthermore, the aromatic monomer is at least one of biphenyl, p-terphenyl, m-terphenyl, p-quaterphenyl, diphenylmethane, 1,2-diphenylethane, 1,3-diphenylpropane, 1,4-diphenylbutane, 1,5-diphenylpentane, 1,6-diphenylhexane, 1,7-diphenylheptane and 1,8-diphenyloctane.

[0020] Preferably, the molar ratio of the branching agent, the monomer containing a hydrophilic group and the monomer containing a piperidone group is (0.005-1):(0.005-3):36.

[0021] Preferably, the molar ratio of the aromatic monomer to the piperidone group-containing monomer is (0.1-3):1.

[0022] Preferably, the monomer polymerization method in step (1) is a super acid polycondensation method or a free radical polymerization method.

[0023] More preferably, the catalyst of the superacid polycondensation method is at least one of trifluoroacetic acid, methanesulfonic acid, trifluoromethanesulfonic acid, pentafluoropropionic acid or heptafluorobutyric acid sulfuric acid; the free radical initiator of the free radical polymerization method is at least one of azobisisobutyronitrile, 1,1'-azobis(cyclohexanecarbonitrile), dimethyl azobisisobutyrate, benzoyl peroxide, and dicyclohexyl peroxydicarbonate.

[0024] More preferably, the temperature of the superacid polycondensation method in step (1) is -10-80°C, and the polymerization time is 0.5 hours to 7 days.

[0025] Preferably, the polymerization solvent in step (1) is at least one of dichloromethane, chloroform, tetrachloroethane and toluene.

[0026] Preferably, the method for introducing the monomer containing a hydrophilic group in step (1) is to first protect the hydrophilic group by a protecting group, and then reduce it to obtain the hydrophilic group through a deprotection process; the protecting group is one of 9,9-bis(methoxymethyl)fluorene, tert-butyldimethylsilyl, and benzyl; and the deprotection reagent is one of tetrabutylammonium fluoride and H2 / Pd-C.

[0027] Preferably, the ionizing agent in step (2) is one of iodomethane, iodoethane, iodopropane, iodobutylane, iodopentane, bromoethane, bromopropane, bromobutylane, bromopentane, bromohexane, bromocyclopropane, bromocyclobutane, bromocyclopentane, 1,2-dibromoethane, 1,3-dibromopropane, 1,4-dibromobutane, 1-5-dibromopentane, 1-6-dibromohexane, iodine hexane, bromocyclohexane, 1,2-diiodoethane, 1,3-diiodopropane, 1,4-diiodobutane, 1-5-diiodopentane, and 1-6-diiodohexane.

[0028] Preferably, the ionizing solvent in step (2) is at least one of dimethyl sulfoxide, 1-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, ethyl acetate, and diethyl ether.

[0029] Preferably, the reaction temperature in step (2) is 5-40° C., and the reaction time is 24 hours to 72 hours.

[0030] Preferably, the organic solvent in step (3) is at least one of chloroform, dichloromethane, tetrahydrofuran, ethyl acetate, dimethyl sulfoxide, 1-methyl-2-pyrrolidone, dimethylformamide, and dimethylacetamide.

[0031] According to another aspect of the present invention, there is provided an anionic binder having both hydrophilicity and dispersibility, which is obtained by any of the above methods for preparing an anionic binder having both hydrophilicity and dispersibility.

[0032] According to another aspect of the present invention, a method for preparing a catalytic layer is provided, wherein the above-mentioned anionic binder and catalyst are formulated into a uniform catalyst ink, the catalyst ink is applied on a membrane or a porous substrate, and after the solvent evaporates, a catalytic layer covered with a hydrophilic anionic binder is obtained.

[0033] Preferably, the catalyst is at least one of a platinum-based catalyst, a palladium-based catalyst, a carbon-based catalyst, and a single-atom catalyst.

[0034] Preferably, the catalyst ink further comprises isopropyl alcohol and ultrapure water.

[0035] Preferably, the coating is performed by spraying or knife coating the catalyst ink on a membrane or porous substrate at 60-80°C.

[0036] Preferably, the porous substrate is one of nickel foam, carbon paper, and carbon cloth.

[0037] A catalytic layer is obtained by any of the above methods for preparing a catalytic layer.

[0038] According to another aspect of the present invention, there is provided an application of an anionic binder having both hydrophilicity and dispersibility for use in alkaline water electrolysis, alkaline fuel cells, carbon dioxide reduction, and flow batteries.

[0039] According to another aspect of the present invention, there is provided an application of a catalyst for alkaline water electrolysis, alkaline fuel cells, carbon dioxide reduction and liquid flow batteries.

[0040] The beneficial effects of the present invention are:

[0041] The present invention provides an anionic binder with both hydrophilicity and dispersibility, as well as a preparation method and application thereof. The preparation process is simple, the processing conditions are mild, and the product conversion rate is high. Compared with conventional anionic binders, the present invention introduces a monomer containing a hydrophilic phenolic hydroxyl group into the main chain containing a triptycene branching agent. The free volume between the main chains can enhance material transport within the binder, reduce the swelling of the binder while the hydrophilic monomer enhances the binder's water absorption, and ensure the mechanical stability of the binder. The piperidine group side chain on the binder ensures effective anionic conduction and chemical stability, resulting in a highly stable and hydrophilic anionic binder while maintaining an anionic conduction rate. The hydrophilic groups and free volume in the anionic binder prepared by the present invention greatly enhance its water absorption and storage capacity. The water absorption rate of the anionic binder reaches 900%, which is 53.6% higher than that of a commercial binder (Piperion) without hydrophilic groups, demonstrating its high hydrophilicity. Furthermore, the hydroxide conductivity of the anionic binder reaches 188 mS / cm at 80 degrees Celsius, and the ion exchange capacity decay rate is less than 8% within 1440 hours, indicating good alkaline stability.

[0042] After the anionic binder is prepared into a catalytic layer, the increased hydrophilicity of the catalytic layer reduces the interfacial energy between water and the catalyst, allowing water molecules to diffuse and penetrate rapidly within the catalytic layer, ensuring sufficient water supply on the cathode side, maintaining the continuous and stable progress of the electrochemical reaction, and improving the efficiency of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The molecular structure diagram of the anionic binder prepared in Example 1;

[0044] Figure 2 The molecular structural formula of the anionic binder prepared in Comparative Example 1;

[0045] Figure 3 is the molecular structural formula diagram of the anionic binder of Comparative Example 3;

[0046] Figure 4This is a comparison chart of the water absorption rates of the anionic binders prepared in Example 1 and Comparative Example 1, as well as the anionic binder prepared in Comparative Example 3 at different temperatures;

[0047] Figure 5 This is a graph showing the alkaline stability of the anionic binder prepared in Example 1;

[0048] Figure 6 This is a water contact angle image of the catalyst layer obtained from the anionic binder solution prepared in Example 1;

[0049] Figure 7 This is the water contact angle image of the catalytic layer obtained from the anionic binder solution of Comparative Example 3. DETAILED DESCRIPTION

[0050] The present invention will be further described in detail below through specific examples. The following examples may enable those skilled in the art to have a more comprehensive understanding of the present invention, but are not intended to limit the present invention in any way.

[0051] The present invention provides an anionic binder having both hydrophilicity and dispersibility and a preparation method thereof, which is prepared according to the following steps:

[0052] (1) Through the monomer polymerization method, a branching agent, a monomer containing a hydrophilic group, an aromatic monomer, and a monomer containing a piperidinone group are polymerized in a polymerization solvent to obtain a polymer with hydrophilicity and a spatial three-dimensional structure.

[0053] As a preferred embodiment, the branching agent is at least one of the monomers represented by formula (1) and formula (2); the monomer containing a hydrophilic group is a monomer represented by formula (3); the aromatic monomer is at least one of the monomers represented by formula (5), formula (6) and formula (7); the monomer containing a piperidone group is a monomer represented by formula (4);

[0054]

[0055] wherein R1 and R2 in formula (3) are each independently selected from any one of phenol, catechol, o-cresol, resorcinol, toluene, methanol, 1-ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, 1-heptanol, 1-octanol, and methoxymethyl;

[0056] Wherein, R3 in formula (4) is selected from any one of hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl or phenyl;

[0057] Wherein, n in formula (5) is an integer from 0 to 10;

[0058] Here, n in formula (6) is an integer from 1 to 20.

[0059] As a more preferred embodiment, the monomer containing a hydrophilic group can be selected from bisphenol fluorene, 9,9-bis(3,4-dihydroxyphenyl)fluorene, 9,9-bis(3-methyl-4-hydroxyphenyl)fluorene, 9,9-bis(6-hydroxy-2-naphthol)fluorene, and 9-fluorenylmethanol.

[0060] As a more preferred embodiment, the monomer containing a piperidone group can be selected from at least one of N-methyl-4-piperidone, N-ethyl-4-piperidone, N-propyl-4-piperidone, 4-piperidone or N-isopropyl-4-piperidone.

[0061] As a more preferred embodiment, the aromatic monomer can be selected from at least one of biphenyl, p-terphenyl, m-terphenyl, p-quaterphenyl, diphenylmethane, 1,2-diphenylethane, 1,3-diphenylpropane, 1,4-diphenylbutane, 1,5-diphenylpentane, 1,6-diphenylhexane, 1,7-diphenylheptane and 1,8-diphenyloctane.

[0062] As a preferred embodiment, the molar ratio of the branching agent, the monomer containing a hydrophilic group and the monomer containing a piperidinone group is (0.005-1):(0.005-3):36.

[0063] As a preferred embodiment, the molar ratio of the aromatic monomer to the monomer containing the piperidinone group is (0.1-3):1.

[0064] As a preferred embodiment, the monomer polymerization method in step (1) is a super acid polycondensation method or a free radical polymerization method.

[0065] As a more preferred embodiment, the catalyst of the superacid polycondensation method can be selected from at least one of trifluoroacetic acid, methanesulfonic acid, trifluoromethanesulfonic acid, pentafluoropropionic acid or heptafluorobutyric acid sulfuric acid; the free radical initiator of the free radical polymerization method can be selected from at least one of azobisisobutyronitrile, 1,1'-azobis(cyclohexanecarbonitrile), dimethyl azobisisobutyrate, benzoyl peroxide, and dicyclohexyl peroxydicarbonate.

[0066] As a more preferred embodiment, the temperature of the superacid polycondensation method in step (1) is -10-80°C, and the polymerization time is 0.5 hours to 7 days.

[0067] As a preferred embodiment, the polymerization solvent in step (1) can be selected from at least one of dichloromethane, chloroform, tetrachloroethane, and toluene.

[0068] As a preferred embodiment, the method for introducing the monomer containing a hydrophilic group in step (1) is to first protect the hydrophilic group by a protecting group, and then reduce it to obtain the hydrophilic group through a deprotection process; the protecting group can be selected from one of 9,9-bis(methoxymethyl)fluorene, tert-butyldimethylsilyl, and benzyl; the deprotection reagent can be selected from one of tetrabutylammonium fluoride and H2 / Pd-C.

[0069] (2) reacting the polymer obtained in step (1) with an ionizing agent in an ionizing solvent under light-shielding conditions to obtain an anionic binder solid having cationic side chains.

[0070] As a preferred embodiment, the ionizing agent in step (2) can be selected from one of iodomethane, iodoethane, iodopropane, iodobutane, iodopentane, bromoethane, bromopropane, bromobutane, bromopentane, bromohexane, bromocyclopropane, bromocyclobutane, bromocyclopentane, 1,2-dibromoethane, 1,3-dibromopropane, 1,4-dibromobutane, 1-5-dibromopentane, 1-6-dibromohexane, iodine hexane, bromocyclohexane, 1,2-diiodoethane, 1,3-diiodopropane, 1,4-diiodobutane, 1-5-diiodopentane, and 1-6-diiodohexane.

[0071] As a preferred embodiment, the ionizing solvent in step (2) can be selected from at least one of dimethyl sulfoxide, 1-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, ethyl acetate, and diethyl ether.

[0072] As a preferred embodiment, the reaction temperature in step (2) is 5-40° C., and the reaction time is 24 hours to 72 hours.

[0073] (3) dissolving the anionic binder solid obtained in step (2) in an organic solvent to obtain a fully dispersed hydrophilic anionic binder solution.

[0074] As a preferred embodiment, the organic solvent in step (3) is at least one of chloroform, dichloromethane, tetrahydrofuran, ethyl acetate, dimethyl sulfoxide, 1-methyl-2-pyrrolidone, dimethylformamide, and dimethylacetamide.

[0075] The anionic binder having both hydrophilicity and dispersibility can be used in alkaline water electrolysis, alkaline fuel cells, carbon dioxide reduction and liquid flow batteries.

[0076] The present invention also provides a catalytic layer and a preparation method thereof, which are prepared according to the following process: the anionic binder of the present invention and the catalyst are mixed into a uniform catalyst ink, the catalyst ink is coated on a membrane or a porous substrate, and after the solvent evaporates, a catalytic layer covered with a hydrophilic anionic binder is obtained.

[0077] As a preferred embodiment, the catalyst particles can be at least one of platinum-based catalysts, palladium-based catalysts, carbon-based catalysts, and single-atom catalyst particles.

[0078] As a preferred embodiment, the catalyst ink further comprises isopropyl alcohol and ultrapure water.

[0079] As a preferred embodiment, the coating is performed by spraying or knife coating the catalyst ink on the membrane or porous substrate at 60-80°C.

[0080] As a preferred embodiment, the porous substrate is one of nickel foam, carbon paper, and carbon cloth.

[0081] The above-mentioned catalytic layer can be used in alkaline water electrolysis, alkaline fuel cells, carbon dioxide reduction and liquid flow batteries.

[0082] Specifically:

[0083] Example 1

[0084] A method for preparing a highly stable, hydrophilic three-dimensional anionic binder is provided, the structure of which is shown below:

[0085]

[0086] The preparation method of the anionic binder is as follows:

[0087] (1) Weigh 0.25 g (1 mmol) of triptycene (1a), 0.96 g (2.75 mmol) of bisphenolfluorene (1b), and 3.83 g (24.8 mmol) of biphenyl (1c) into a 100 mL cooling circulator. Add 4.1 g (35.9 mmol) of N-methyl-4-piperidone (1d) and 24 mL of anhydrous dichloromethane. Add 3.6 mL of trifluoroacetic acid and 24 mL of trifluoromethanesulfonic acid at 0°C and react for 48 hours. Transfer the solid purple product to a saturated K2CO3 solution and wash for 24 hours, then wash in methanol for 24 hours, and then wash in deionized water for 24 hours. Filter and dry to obtain a white solid product.

[0088] (2) 0.4 g of the above product was added to 20 mL of dimethyl sulfoxide, followed by 0.17 g of anhydrous potassium carbonate and 0.2 g of iodomethane. The mixture was reacted in the dark at room temperature for 24 hours. The reaction solution was poured into ethyl acetate for precipitation, filtered, washed three times with deionized water, and dried to obtain an anion exchange polymer.

[0089] (3) The obtained anionic binder solid is dissolved in dimethyl sulfoxide, and ultrasonically treated to obtain a fully dispersed, highly stable, hydrophilic anionic binder solution.

[0090] (5) A 20 wt% breathable anionic binder solution was ultrasonically mixed with commercial catalyst Pt / C particles, deionized water, and isopropyl alcohol to prepare a uniform catalyst ink, which was sprayed onto an anion exchange membrane at 60°C. After the solvent evaporated, a highly stable, hydrophilic ionic binder-covered catalyst layer was obtained.

[0091] Example 2

[0092] A method for preparing a highly stable, hydrophilic three-dimensional anionic binder is provided, the structure of which is shown below:

[0093]

[0094] The preparation method of the anionic binder is as follows:

[0095] (1) Weigh 0.3 g (1 mmol) of triphenylbenzene (2a), 1.05 g (2.75 mmol) of 9,9-bis(3,4-dihydroxyphenyl)fluorene (2b), and 5.72 g (24.8 mmol) of m-terphenyl (2c) into a 100 mL cooling circulator. Add 4.1 g (35.9 mmol) of N-methyl-4-piperidone (2d) and 24 mL of anhydrous dichloromethane. Add 3.6 mL of trifluoroacetic acid and 24 mL of trifluoromethanesulfonic acid at 0°C and react for 48 hours. Transfer the solid purple product to a saturated K2CO3 solution and wash for 24 hours, then in methanol for 24 hours, and in deionized water for 24 hours. Filter and dry to obtain a white solid product.

[0096] (2) 0.4 g of the above product was added to 20 mL of dimethyl sulfoxide, followed by 0.17 g of anhydrous potassium carbonate and 0.2 g of iodomethane. The mixture was reacted in the dark at room temperature for 24 hours. The reaction solution was poured into ethyl acetate for precipitation, filtered, washed three times with deionized water, and dried to obtain an anion exchange polymer.

[0097] (3) The obtained anionic binder solid is dissolved in dimethyl sulfoxide, and ultrasonically treated to obtain a fully dispersed, highly stable, hydrophilic anionic binder solution.

[0098] (5) A 10 wt% breathable anionic binder solution was ultrasonically mixed with commercial catalyst Pt / C particles, deionized water, and isopropyl alcohol to prepare a uniform catalyst ink, which was sprayed onto an anion exchange membrane at 60°C. After the solvent evaporated, a highly stable, hydrophilic ionic binder-covered catalyst layer was obtained.

[0099] Example 3

[0100] A method for preparing a highly stable, hydrophilic three-dimensional anionic binder is provided, the structure of which is shown below:

[0101]

[0102] The preparation method of the anionic binder is as follows:

[0103] (1) Weigh 0.25 g (1 mmol) of triptycene (3a), 1.04 g (2.75 mmol) of 9,9-bis(3-methyl-4-hydroxyphenyl)fluorene (3b), and 5.72 g (24.8 mmol) of p-terphenyl (3c) into a 100 mL cooling circulator. Add 4.1 g (35.9 mmol) of N-methyl-4-piperidone (3d) and 24 mL of anhydrous dichloromethane. Add 3.6 mL of trifluoroacetic acid and 24 mL of trifluoromethanesulfonic acid at 0°C and react for 48 hours. Transfer the solid purple product to a saturated K2CO3 solution and wash for 24 hours, then in methanol for 24 hours, and then in deionized water for 24 hours. Filter and dry to obtain a white solid product.

[0104] (2) 0.4 g of the above product was added to 20 mL of dimethyl sulfoxide, followed by 0.17 g of anhydrous potassium carbonate and 0.2 g of iodomethane. The mixture was reacted in the dark at room temperature for 24 hours. The reaction solution was poured into ethyl acetate for precipitation, filtered, washed three times with deionized water, and dried to obtain an anion exchange polymer.

[0105] (3) The obtained anionic binder solid is dissolved in dimethyl sulfoxide, and ultrasonically treated to obtain a fully dispersed, highly stable, hydrophilic anionic binder solution.

[0106] (5) A 20 wt% breathable anionic binder solution was ultrasonically mixed with commercial catalyst Pt / C particles, deionized water, and isopropyl alcohol to prepare a uniform catalyst ink, which was sprayed onto an anion exchange membrane at 60°C. After the solvent evaporated, a highly stable, hydrophilic ionic binder-covered catalyst layer was obtained.

[0107] Example 4

[0108] A method for preparing a highly stable, hydrophilic three-dimensional anionic binder is provided, the structure of which is shown below:

[0109]

[0110] The preparation method of the anionic binder is as follows:

[0111] (1) Weigh 0.25 g (1 mmol) of triptycene (4a), 0.96 g (2.75 mmol) of bisphenolfluorene (4b), and 5.72 g (24.8 mmol) of p-terphenyl (4c) into a 100 mL cooling circulator. Add 4.1 g (35.9 mmol) of N-methyl-4-piperidone (4d) and 24 mL of anhydrous dichloromethane. Add 3.6 mL of trifluoroacetic acid and 24 mL of trifluoromethanesulfonic acid at 0°C and react for 48 hours. Transfer the solid purple product to a saturated K2CO3 solution and wash for 24 hours, then in methanol for 24 hours, and then in deionized water for 24 hours. Filter and dry to obtain a white solid product.

[0112] (2) 0.4 g of the above product was added to 20 mL of dimethyl sulfoxide, followed by 0.17 g of anhydrous potassium carbonate and 0.2 g of iodomethane. The mixture was reacted in the dark at room temperature for 24 hours. The reaction solution was poured into ethyl acetate for precipitation, filtered, washed three times with deionized water, and dried to obtain an anion exchange polymer.

[0113] (3) The obtained anionic binder solid is dissolved in dimethyl sulfoxide, and ultrasonically treated to obtain a fully dispersed, highly stable, hydrophilic anionic binder solution.

[0114] (5) A 20 wt% breathable anionic binder solution was ultrasonically mixed with commercial catalyst Pt / C particles, deionized water, and isopropyl alcohol to prepare a uniform catalyst ink, which was sprayed onto an anion exchange membrane at 60°C. After the solvent evaporated, a highly stable, hydrophilic ionic binder-covered catalyst layer was obtained.

[0115] Example 5

[0116] A method for preparing a highly stable, hydrophilic three-dimensional anionic binder is provided, the structure of which is shown below:

[0117]

[0118]

[0119] The preparation method of the anionic binder is as follows:

[0120] (1) Weigh 0.125 g (0.5 mmol) of triptycene (1a), 0.5 g (1.43 mmol) of bisphenolfluorene (1b), and 3.83 g (24.8 mmol) of biphenyl (1c) into a 100 mL cooling circulator. Add 4.1 g (35.9 mmol) of N-methyl-4-piperidone (1d) and then 24 mL of anhydrous dichloromethane. Add 3.6 mL of trifluoroacetic acid and 20 mL of trifluoromethanesulfonic acid at 0°C and react for 36 hours. Transfer the solid purple product to a saturated K2CO3 solution and wash for 24 hours, then in methanol for 24 hours, and then in deionized water for 24 hours. Filter and dry to obtain a white solid product.

[0121] (2) 0.4 g of the above product was added to 20 mL of dimethyl sulfoxide, followed by 0.17 g of anhydrous potassium carbonate and 0.2 g of iodomethane. The mixture was reacted in the dark at room temperature for 48 hours. The reaction solution was poured into ethyl acetate for precipitation, filtered, washed three times with deionized water, and dried to obtain an anion exchange polymer.

[0122] (3) The obtained anionic binder solid is dissolved in dimethyl sulfoxide, and ultrasonically treated to obtain a fully dispersed, highly stable, hydrophilic anionic binder solution.

[0123] (5) A 20 wt% breathable anionic binder solution was ultrasonically mixed with commercial catalyst Pt / C particles, deionized water, and isopropyl alcohol to prepare a uniform catalyst ink, which was sprayed onto an anion exchange membrane at 60°C. After the solvent evaporated, a highly stable, hydrophilic ionic binder-covered catalyst layer was obtained.

[0124] Example 6

[0125] A method for preparing a highly stable, hydrophilic three-dimensional anionic binder is provided, the structure of which is shown below:

[0126]

[0127] The preparation method of the anionic binder is as follows:

[0128] (1) Weigh 0.25 g (1 mmol) of triptycene (1a), 0.96 g (2.75 mmol) of bisphenolfluorene (1b), and 3.83 g (24.8 mmol) of biphenyl (1c) into a 100 mL cooling circulator. Add 4.1 g (35.9 mmol) of N-methyl-4-piperidone (1d) and 24 mL of anhydrous dichloromethane. Add 3.6 mL of trifluoroacetic acid and 24 mL of trifluoromethanesulfonic acid at 0°C and react for 48 hours. Transfer the solid purple product to a saturated K2CO3 solution and wash for 24 hours, then wash in methanol for 24 hours, and then wash in deionized water for 24 hours. Filter and dry to obtain a white solid product.

[0129] (2) 0.4 g of the above product was added to 20 mL of dimethyl sulfoxide, followed by 0.17 g of anhydrous potassium carbonate and 0.2 g of methyl iodide. The mixture was heated at 40°C in the dark for 24 hours. The reaction solution was poured into diethyl ether for precipitation, filtered, washed three times with deionized water, and dried to obtain an anion exchange polymer.

[0130] (3) The obtained anionic binder solid is dissolved in dimethyl sulfoxide, and ultrasonically treated to obtain a fully dispersed, highly stable, hydrophilic anionic binder solution.

[0131] (5) A 20 wt% breathable anionic binder solution was ultrasonically mixed with commercial catalyst Pt / C particles, deionized water, and isopropyl alcohol to prepare a uniform catalyst ink, which was sprayed onto an anion exchange membrane at 60°C. After the solvent evaporated, a highly stable, hydrophilic ionic binder-covered catalyst layer was obtained.

[0132] Example 7

[0133] A method for preparing a highly stable, hydrophilic three-dimensional anionic binder is provided, the structure of which is shown below:

[0134]

[0135] The preparation method of the anionic binder is as follows:

[0136] (1) Weigh 0.0125 g (0.05 mmol) of triptycene (7a), 1.05 g (2.75 mmol) of 9,9-bis(3,4-dihydroxyphenyl)fluorene (7b), and 3.83 g (24.8 mmol) of biphenyl (7c) into a 100 mL cooling circulator. Add 4.1 g (35.9 mmol) of N-methyl-4-piperidone (7d) and 24 mL of anhydrous dichloromethane. Add 3.6 mL of trifluoroacetic acid and 20 mL of trifluoromethanesulfonic acid at 0°C and react for 36 hours. Transfer the solid purple product to a saturated K2CO3 solution and wash for 24 hours, then wash in methanol for 24 hours, and then wash in deionized water for 24 hours. Filter and dry to obtain a white solid product.

[0137] (2) 0.4 g of the above product was added to 20 mL of dimethyl sulfoxide, followed by 0.17 g of anhydrous potassium carbonate and 0.2 g of iodomethane. The mixture was reacted in the dark at room temperature for 48 hours. The reaction solution was poured into ethyl acetate for precipitation, filtered, washed three times with deionized water, and dried to obtain an anion exchange polymer.

[0138] (3) The obtained anionic binder solid is dissolved in dimethyl sulfoxide, and ultrasonically treated to obtain a fully dispersed, highly stable, hydrophilic anionic binder solution.

[0139] (5) A 20 wt% breathable anionic binder solution was ultrasonically mixed with commercial catalyst Pt / C particles, deionized water, and isopropyl alcohol to prepare a uniform catalyst ink, which was sprayed onto an anion exchange membrane at 60°C. After the solvent evaporated, a highly stable, hydrophilic ionic binder-covered catalyst layer was obtained.

[0140] Comparative Example 1

[0141] The preparation method of the anionic binder includes the following structure:

[0142]

[0143] The preparation method of the anionic binder is as follows:

[0144] (1) 0.363 g (1.45 mmol) of triptycene (8a), 0.369 g (1.9 mmol) of 9,9-dimethylfluorene (8b), and 2.639 g (17.1 mmol) of biphenyl (8c) were weighed into a 100 mL cooling circulator. 2.8 g (25.4 mmol) of N-methyl-4-piperidone (8d) was added, followed by 24 mL of anhydrous dichloromethane. 3.6 mL of trifluoroacetic acid and 30 mL of trifluoromethanesulfonic acid were added at 0°C and reacted for 2 hours. The solid blue product was transferred to a saturated K2CO3 solution and washed at 60°C for 12 hours, then washed in methanol for 24 hours, and then washed in deionized water for 24 hours. After filtration and drying, a white solid product was obtained.

[0145] (2) 4.1 g of the above product was added to 100 mL of dimethyl sulfoxide, followed by 1.725 g of anhydrous potassium carbonate and 2.11 g of methyl iodide. The mixture was reacted in the dark at room temperature for 24 hours. The reaction solution was poured into ethyl acetate for precipitation, filtered, washed three times with deionized water, and dried to obtain an anion exchange polymer.

[0146] (3) The obtained anionic binder solid is dissolved in dimethyl sulfoxide, and ultrasonically treated to obtain an anionic binder solution.

[0147] (5) A 20 wt% anionic binder solution was ultrasonically mixed with commercial catalyst Pt / C particles, deionized water, and isopropyl alcohol to prepare a uniform catalyst ink, which was sprayed onto an anion exchange membrane at 60°C. After the solvent evaporated, a catalyst layer covered with an ionic binder was obtained.

[0148] Comparative Example 2

[0149] The preparation method of the anionic binder includes the following structure:

[0150]

[0151]

[0152] The preparation method of the anionic binder is as follows:

[0153] (1) Weigh 0.363 g (1.45 mmol) of triptycene (9a), 1.23 g (6.75 mmol) of 1,2-diphenylethane (9b), and 4.663 g (20 mmol) of p-terphenyl (9c) in a 100 mL cooling circulator. Add 3.87 g (35 mmol) of N-methyl-4-piperidone (9d) and then 24 mL of anhydrous dichloromethane. Add 3.6 mL of trifluoroacetic acid and 30 mL of trifluoromethanesulfonic acid at 0°C and react for 2 hours. Transfer the solid blue product to a saturated K2CO3 solution and wash at 60°C for 12 hours, then wash in methanol for 24 hours, and then wash in deionized water for 24 hours. Filter and dry to obtain a white solid product.

[0154] (2) 4.35 g of the above product was added to 100 mL of dimethyl sulfoxide, followed by 1.725 g of anhydrous potassium carbonate and 2.11 g of iodomethane. The mixture was reacted in the dark at room temperature for 24 hours. The reaction solution was poured into ethyl acetate for precipitation, filtered, washed three times with deionized water, and dried to obtain an anion exchange polymer.

[0155] (3) The obtained anionic binder solid is dissolved in dimethyl sulfoxide, and ultrasonically treated to obtain an anionic binder solution.

[0156] (5) A 20 wt% anionic binder solution was ultrasonically mixed with commercial catalyst Pt / C particles, deionized water, and isopropyl alcohol to prepare a uniform catalyst ink, which was sprayed onto an anion exchange membrane at 60°C. After the solvent evaporated, a catalyst layer covered with an ionic binder was obtained.

[0157] Comparative Example 3

[0158] This proposal provides an anion exchange membrane polymer PiperION-A40, produced by Versogen.

[0159] Comparative Example 4

[0160] Relative to Example 1, the molar ratio was changed to prepare an anionic binder, the structure of which is shown below:

[0161]

[0162] The preparation method of the anionic binder is as follows:

[0163] (1) Weigh 0.5 g (2 mmol) of triptycene (10a), 0.96 g (2.75 mmol) of bisphenolfluorene (10b), and 3.83 g (24.8 mmol) of biphenyl (10c) into a 100 mL cooling circulator. Add 4.1 g (35.9 mmol) of N-methyl-4-piperidone (10d) and 24 mL of anhydrous dichloromethane. Add 3.6 mL of trifluoroacetic acid and 24 mL of trifluoromethanesulfonic acid at 0°C and react for 72 hours. Transfer the solid purple product to a saturated K2CO3 solution and wash for 24 hours, then in methanol for 24 hours, and then in deionized water for 24 hours. Filter and dry to obtain a white powder product.

[0164] (2) 0.4 g of the above product was added to 20 mL of dimethyl sulfoxide, followed by 0.17 g of anhydrous potassium carbonate and 0.2 g of iodomethane. The mixture was allowed to react at room temperature in the dark for 24 hours. The reaction solution was poured into ethyl acetate, but no precipitation occurred.

[0165] Comparative Example 5

[0166] Relative to Example 1, the molar ratio was changed to prepare an anionic binder, the structure of which is shown below:

[0167]

[0168] The preparation method of the anionic binder is as follows:

[0169] (1) 0.25 g (1 mmol) of triptycene (11a), 3.5 g (10 mmol) of bisphenolfluorene (11b), and 3.83 g (24.8 mmol) of biphenyl (11c) were weighed into a 100 mL cooling circulator. 4.1 g (35.9 mmol) of N-methyl-4-piperidone (11d) was added, followed by 24 mL of anhydrous dichloromethane. 3.6 mL of trifluoroacetic acid and 24 mL of trifluoromethanesulfonic acid were added at 0°C and the reaction was allowed to proceed for 72 hours. The purple liquid product was transferred to a saturated K2CO3 solution, where it swelled and decomposed.

[0170] Comparative Example 6

[0171] A method for preparing a three-dimensional adhesive is provided, the structure of which is as follows:

[0172]

[0173] The preparation method of the anionic binder is as follows:

[0174] (1) 0.25 g (1 mmol) of triptycene (12a), 0.96 g (2.75 mmol) of bisphenolfluorene (12b), and 3.83 g (24.8 mmol) of biphenyl (12c) were weighed into a 100 mL cooling circulator, followed by the addition of 24 mL of anhydrous dichloromethane. 3.6 mL of trifluoroacetic acid and 15 mL of trifluoromethanesulfonic acid were added at 0°C and reacted for 0.5 hours. The solid blue product was transferred to a saturated K2CO3 solution and washed for 24 hours, then washed in methanol for 24 hours, and then washed in deionized water for 24 hours. After filtration and drying, a white solid product without ion conductivity was obtained.

[0175] Comparative Example 7

[0176] A method for preparing a highly stable, hydrophilic three-dimensional anionic binder is provided, the structure of which is shown below:

[0177]

[0178] The preparation method of the anionic binder is as follows:

[0179] (1) 0.0125 g (0.05 mmol) of triptycene (13a), 1.35 g (3.5 mmol) of 9,9-bis(3,4-dihydroxyphenyl)fluorene (13b), and 3.83 g (24.8 mmol) of biphenyl (13c) were weighed into a 100 mL cooling circulator. 4.1 g (35.9 mmol) of N-methyl-4-piperidone (13d) was added, followed by 24 mL of anhydrous dichloromethane. 3.6 mL of trifluoroacetic acid and 20 mL of trifluoromethanesulfonic acid were added at 0°C and the reaction was allowed to proceed for 72 hours. The purple liquid product was transferred to a saturated K2CO3 solution, where it swelled and decomposed.

[0180] In Examples 1-4 above, anionic binders with varying hydrophilicity and water absorption were obtained by adjusting the monomers involved in the polycondensation reaction. In Example 5 above, compared to Example 1, an anionic binder with the same hydrophilicity was obtained by adjusting the molar ratio of the monomers involved in the polycondensation reaction. In Example 6 above, an anionic binder with the same hydrophilicity was obtained by adjusting the reaction temperature and time in step 2. In Example 7 above, anionic binders with varying hydrophilicity and water absorption were obtained by adjusting the type and molar ratio of the monomers involved in the polycondensation reaction.

[0181] In the above comparative example 1, a low hydrophilic anionic binder is prepared by introducing a non-hydrophilic group (7b), which is used for comparison with Example 1 of the present invention; in the above comparative example 2, a low hydrophilic anionic binder is prepared by introducing a non-hydrophilic group (8b), which is used for comparison with Example 3 of the present invention; in the above comparative example 3, the structure contains a hydrophobic group and does not have a stereo conformation, which is used for comparison with the embodiment of the present invention. In the above comparative example 4, due to the increase in the molar ratio of the branching agent (triptycene) with a rigid structure, the structural rigidity of the intermediate product obtained in step 1 is too large and the degree of polymerization is too low; Examples 1-7 show that in order to successfully obtain the intermediate product of step 1, the molar ratio of the branching agent to the monomer containing the piperidinone group in step 1 is preferably controlled at (0.005-1):36. In Comparative Examples 5 and 7 above, due to the increased molar ratio of the monomer containing a hydrophilic group, the increase in the phenolic hydroxyl content in the hydrophilic group hinders the polymerization process of the super acid condensation and greatly increases the hydrophilicity of the intermediate product of step 1, causing it to dissolve in water; Examples 1-7 show that in order to successfully obtain the intermediate product of step 1, the molar ratio of the monomer containing a hydrophilic group to the monomer containing a piperidone group in step 1 is preferably controlled at (0.005-3):36. In Comparative Example 6 above, a monomer containing a piperidone group was not introduced, and a binder without ion conductivity was obtained for comparison with the embodiments of the present invention.

[0182] Figure 1 Figure 1 shows the molecular structure of the anionic binder of Example 1. It can be seen that the introduction of the branching agent into the polymer preserves the hydrophilic phenolic hydroxyl groups. The presence of the branching agent enhances the three-dimensional conformation of the polymer molecules, thereby expanding the free volume of the polymer. The presence of the phenolic hydroxyl groups enables hydrogen bonding with water molecules, increasing the hydrophilicity of the binder and thus enhancing its hydrophilic degassing properties in practical applications.

[0183] Figure 2 The molecular structure diagram of the commercial anionic binder of Comparative Example 1 shows that, compared with Example 1, there is no hydrophilic group inside the molecular structure, but it also has a three-dimensional conformation.

[0184] Figure 3 The molecular structure diagram of the commercial anionic binder (PiperION) of Comparative Example 3 shows that the polymer binder not only does not have a three-dimensional ionic conformation, but also does not contain a hydrophilic group.

[0185] Figure 4This is a comparison chart of the water absorption rates of the anionic binders of Example 1 and Comparative Examples 1 and 3. It can be seen that the water absorption rate of Example 1 having a three-dimensional conformation and hydrophilic groups is 1.8 times that of Comparative Example 1 without a hydrophilic group, and is more than 20 times that of Comparative Example 3 having neither a three-dimensional ionic conformation nor a hydrophilic group.

[0186] Figure 5 This is an alkaline stability image of the anionic binder obtained in Example 1. In 1 mol / L potassium hydroxide at 80 degrees Celsius, the ion exchange capacity decay rate of the anionic binder obtained in Example 1 is less than 8% within 1440 hours.

[0187] Figure 6 This is an image of the water contact angle of the catalyst layer prepared with the anionic binder of Example 1. 3 seconds after the water droplet contacts the catalyst layer, the water droplet is completely absorbed by the catalyst layer.

[0188] Figure 7 This is a water contact angle image of the catalyst layer prepared with a commercial anionic binder (PiperION) solution in Comparative Example 3. 30 seconds after the water droplet contacts the catalyst layer, the contact angle of the water droplet on the catalyst layer is still 33.3 degrees.

[0189] In summary, a kind of high stability proposed by the present invention, the preparation method of hydrophilic three-dimensional anionic binder, is that piperidine group is connected to the main chain with three-dimensional conformation as side chain, the free volume increased between main chain provides space for the entry of water molecules, and the retention of hydrophilic group on main chain skeleton strengthens the hydrophilicity (water absorption) of the ionomer, and its water absorption capacity is improved by 20 times compared with the commercial binder (PiperION) without hydrophilic group. The promotion of hydrophilicity promotes the reaction solution to be exposed to catalyst for reaction, and also accelerates gas discharge, improves the utilization rate of catalyst, and ensures the mechanical stability of catalytic layer. Meanwhile, the introduction of three-dimensional conformation increases the spatial free volume of binding agent, reduces the swelling of binding agent, and ensures the structural stability of catalytic layer. The introduction of piperidine group has better alkali stability than benzyl ammonium group, and the ion exchange capacity decay rate of the binding agent obtained is less than 8% in 1440 hours. The anionic binder prepared by the present invention, which has high adhesion, stability and high hydrophilicity, can form a uniform colloidal solution in an organic solvent. The anionic binder solution can form a uniform catalyst ink with commercial catalyst particles. After drying, a catalyst layer covered with an ionic binder with high stability and high hydrophilicity is obtained, making it more suitable for use as an anion exchange ionomer in fuel cells and electrolytic cells.

[0190] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments. The above-mentioned specific embodiments are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the present invention and the claims. These all fall within the scope of protection of the present invention.

Claims

1. A method for preparing an anionic binder having both hydrophilicity and dispersibility, characterized in that: The method proceeds as follows: (1) polymerizing a branching agent, a monomer containing a hydrophilic group, an aromatic monomer, and a monomer containing a piperidinone group in a polymerization solvent to obtain a polymer having hydrophilicity and a three-dimensional structure; (2) reacting the polymer obtained in step (1) with an ionizing agent in an ionizing solvent under light-shielding conditions to obtain an anionic binder solid having cationic side chains; (3) dissolving the anionic binder solid obtained in step (2) in an organic solvent to obtain a fully dispersed hydrophilic anionic binder solution.

2. The method for preparing a hydrophilic and dispersible anionic binder according to claim 1, wherein: The branching agent is at least one of the monomers represented by formula (1) and formula (2); the monomer containing a hydrophilic group is a monomer represented by formula (3); the aromatic monomer is at least one of the monomers represented by formula (5), formula (6) and formula (7); the monomer containing a piperidone group is a monomer represented by formula (4); wherein R1 and R2 in formula (3) are each independently selected from any one of phenol, catechol, o-cresol, resorcinol, toluene, methanol, 1-ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, 1-heptanol, 1-octanol, and methoxymethyl; Wherein, R3 in formula (4) is selected from any one of hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl or phenyl; Wherein, n in formula (5) is an integer from 0 to 10; Here, n in formula (6) is an integer from 1 to 20.

3. The method for preparing anionic binder according to claim 2, characterized in that: The monomer containing a hydrophilic group is one of bisphenol fluorene, 9,9-bis(3,4-dihydroxyphenyl)fluorene, 9,9-bis(3-methyl-4-hydroxyphenyl)fluorene, 9,9-bis(6-hydroxy-2-naphthol)fluorene, and 9-fluorenylmethanol; The monomer containing a piperidone group is at least one of N-methyl-4-piperidone, N-ethyl-4-piperidone, N-propyl-4-piperidone, 4-piperidone or N-isopropyl-4-piperidone; The aromatic monomer is at least one of biphenyl, p-terphenyl, m-terphenyl, p-quaterphenyl, diphenylmethane, 1,2-diphenylethane, 1,3-diphenylpropane, 1,4-diphenylbutane, 1,5-diphenylpentane, 1,6-diphenylhexane, 1,7-diphenylheptane and 1,8-diphenyloctane.

4. The method for preparing anionic binder according to claim 1, characterized in that: The molar ratio of the branching agent, the monomer containing a hydrophilic group, and the monomer containing a piperidinone group is (0.005-1):(0.005-3):36; The molar ratio of the aromatic monomer to the monomer containing a piperidinone group is (0.1-3):

1.

5. The method for preparing anionic binder according to claim 1, characterized in that: The monomer polymerization method in step (1) is a super acid polycondensation method or a free radical polymerization method; The catalyst of the superacid polycondensation method is at least one of trifluoroacetic acid, methanesulfonic acid, trifluoromethanesulfonic acid, pentafluoropropionic acid or heptafluorobutyric acid sulfuric acid; the free radical initiator of the free radical polymerization method is at least one of azobisisobutyronitrile, 1,1'-azobis(cyclohexanecarbonitrile), dimethyl azobisisobutyrate, benzoyl peroxide, and dicyclohexyl peroxydicarbonate; The temperature of the superacid polycondensation method is -10-80°C, and the polymerization time is 0.5 hours to 7 days.

6. The method for preparing anionic binder according to claim 1, characterized in that: The polymerization solvent in step (1) is at least one of dichloromethane, chloroform, tetrachloroethane, and toluene; The method for introducing the monomer containing a hydrophilic group in step (1) is to first protect the hydrophilic group by a protecting group, and then reduce it to obtain the hydrophilic group through a deprotection process; the protecting group is one of 9,9-bis(methoxymethyl)fluorene, tert-butyldimethylsilyl, and benzyl; the deprotection reagent is one of tetrabutylammonium fluoride and H2 / Pd-C.

7. The method for preparing anionic binder according to claim 1, characterized in that: The ionizing agent in step (2) is one of iodomethane, iodoethane, iodopropane, iodobutane, iodopentane, bromoethane, bromopropane, bromobutane, bromopentane, bromohexane, bromocyclopropane, bromocyclobutane, bromocyclopentane, 1,2-dibromoethane, 1,3-dibromopropane, 1,4-dibromobutane, 1-5-dibromopentane, 1-6-dibromohexane, iodine, bromocyclohexane, 1,2-diiodoethane, 1,3-diiodopropane, 1,4-diiodobutane, 1-5-diiodopentane, and 1-6-diiodohexane. The ionizing solvent in step (2) is at least one of dimethyl sulfoxide, 1-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, ethyl acetate, and diethyl ether; The reaction temperature in step (2) is 5-40° C., and the reaction time is 24 hours to 72 hours; The organic solvent in step (3) is at least one of chloroform, dichloromethane, tetrahydrofuran, ethyl acetate, dimethyl sulfoxide, 1-methyl-2-pyrrolidone, dimethylformamide, and dimethylacetamide.

8. An anionic binder having both hydrophilicity and dispersibility, characterized in that: The invention is obtained by the preparation method of the anionic binder with both hydrophilicity and dispersibility according to any one of claims 1 to 16.

9. A method for preparing a catalytic layer, characterized in that: The anionic binder as claimed in claim 17 is mixed with catalyst particles to form a uniform catalyst ink, which is then coated on a membrane or a porous substrate. After the solvent evaporates, a hydrophilic anionic binder-covered catalyst layer is obtained.

10. A catalytic layer, characterized in that: Obtained by the preparation method of the catalytic layer according to any one of claims 18 to 22.

Citation Information

Patent Citations

  • Piperidine tertiary amine group polymer based on carbon-based skeleton spatial entanglement structure and application of piperidine tertiary amine group polymer

    CN115558088A